A convenient model of serum-induced reactivity of human astrocytes to investigate astrocyte-derived extracellular vesicles - White, Katherine E.; Bailey, Hannah L.; Shaw, Barry S.; Geiszler, Philippine C.; Mesquita-Ribeiro, Raquel; Scott, Daniel; Layfield, Robert; Serres, Sébastien (Frontiers in Cellular Neuroscience, 2024)
Extracellular vesicles (EVs) are secreted by all cells in the CNS, including neurones and astrocytes. EVs are lipid membrane enclosed particles loaded with various bioactive cargoes reflecting the dynamic activities of cells of origin. In contrast to neurones, the specific role of EVs released by astrocytes is less well understood, partly due to the difficulty in maintaining primary astrocyte cultures in a quiescent state. The aim of this study was to establish a human serum-free astrocyte culture system that maintains primary astrocytes in a quiescent state to study the morphology, function, and protein cargoes of astrocyte-derived EVs.Serum-free medium with G5 supplement and serum-supplemented media medium with 2% FBS were compared for the culture of commercially available human primary foetal astrocytes.Serum-free astrocytes displayed morphologies similar to in vivo astrocytes, and surprisingly, higher levels of astrocyte markers compared to cells astrocytes chronically cultured in serumFBS. In contrast, astrocyte and inflammatory markers in serum-free astrocytes were upregulated 24 h after either acute 2% FBS or cytokine exposure, confirming their capacity to become reactive. Importantly, this suggests that distinct signalling Astrocyte and inflammatory makers in serum-free astrocytes were upregulated 24 h after subsequent serum or cytokine exposure, pathways are involved in acute and chronic astrocyte reactivityconfirming their capacity to become reactive. Despite having a similar morphology, chronically serum-cultured astrocyte-derived EVs (ADEVs) were smaller in size compared to serum-free ADEVs and could reactivate serum-free astrocytes. Proteomic analysis identified distinct protein datasets for both types of ADEVs with enrichment of complement and coagulation cascades, offering insights into their roles in the CNS.Collectively, these results suggest that human primary astrocytes cultured in serum-free media medium bear similarities with in vivo quiescent astrocytes and the addition of serum induces 4 multiple morphological and transcriptional changes that are specific to human reactive astrocytes and their ADEVs. Thus, more emphasis should be made on using multiple structural, molecular, and functional parameters when evaluating ADEVs as biomarkers of astrocyte health.